Relationship between maternal ABO blood groups and pregnancy outcomes: a retrospective cohort study in Dongguan, China - Jing-Yun Yu; Bi Jiang; Xin-Jian Zhang; Si-Si Wei; Wei-Chao He (Taylor & Francis Group, 2023)
The purpose of this study was to study the relationship between maternal ABO blood groups and pregnancy outcomes. A total of 29,658 couples in Dongguan were selected as the research subjects. We obtained data on ABO blood groups and pregnancy outcomes and explored the relationship between them through log binomial regression and survival analysis. Compared to mothers with type B blood, the RR of foetal stillbirth in mothers with type A blood was 2.87 (95% CI: 1.70, 4.85), and compared to mothers with type O blood, the RR was 1.72 (95% CI: 1.16, 2.55). Compared with foetuses of other three blood type mothers, foetuses of A blood type mothers have a higher median birth weight (P = 0.011). Other pregnancy outcomes, including preterm birth, macrosomia, caesarean section, multiple births, birth defects, low birth weight, foetal sex, gestational days, birth length, and APGAR score, were not significantly different. The relationship between maternal ABO blood type and pregnancy outcomes was not affected by paternal blood type. More studies are needed to confirm these results.